The use of selected physiotherapeutic procedures in a patient after post-traumatic skin transplantation in the area of the lower leg and foot - case report - Lewandowska, Anna; Ratuszek-Sadowska, Dorota; Kuczma, Monika; Porzych, Piotr; Stępowska, Justyna; Kowalski, Mikołaj; Hagner-Derengowska, Magdalena (Journal of Education, Health and Sport, 2017)
Skin is an important organ of the senses, acts as a protective barrier to protect our body against physical, chemical and biological factors. In cases of extensive injuries, postoperative complications or infections, a skin transplant may be necessary. It is important that the patient after the surgical intervention can return to health and full physical fitness as soon as possible. A team of specialists together with a physiotherapist is essential to treat the patient. The case describes a patient who got traffic accident and suffered extensive traumatic wounds and a lower limb tissue defect that was stocked with autogenic transplant. As a result of the injuries suffered, the patient experienced pain and discomfort and reduced daily activities. After the kinesiotherapeutic intervention, the patient’s condition has improved significantly, affecting the positive aspect of changing the quality of life.